Kinetic correlation between aldehyde/enamine stereoisomers in reactions between aldehydes with alpha-stereocenters and chiral pyrrolidine-based catalysts - Bures,J; Armstrong,A; Blackmond,DG (CHEMICAL SCIENCE, 2012)
The formation of enamines between aldehydes with alpha-stereocenters and pyrrolidine-based catalysts that lack an acidic proton is examined by kinetic and spectroscopic studies. The reaction exhibits “kinetic stereospecificity” in that each enantiomer of the aldehyde initially reacts to form a specific enamine stereoisomer, prior to thermodynamic equilibration of the E and Z enamines. For the case of prolinate catalysts, each of the stereoisomeric enamines is correlated with a specific stereoisomeric oxazolidinone. The reactions of E and Z enamines with electrophiles such as DEAD lead to products of opposite stereochemistry. The product enantioselectivity observed depends on the extent to which the E and Z enamines are pre-equilibrated prior to reaction with the electrophile. General implications for selectivity in organocatalytic reactions are discussed.